1991
DOI: 10.1021/es00013a008
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic toxicity study of ozonated and ozonated/chlorinated humic acids in Sprague-Dawley rats: a model system for drinking water disinfection

Abstract: Male and female Sprague-Dawley rats were administered drinking water containing humic acids either nondisinfected or following ozonation (03) or ozonation/ chlorination (03/Cl2) for 90 consecutive days. Test animals drank either of two concentrations of humic acids, 0.25 and 1.0 g/L total organic carbon (TOC), while controls received phosphate-buffered, distilled water. No consistent significant treatment-related effects were observed in body weight gain, organ weights, food or water consumption, or hematologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…3,4 Moreover, HAs are precursors of disinfection byproducts (DBPs) such as halogen-organics that are formed after water chlorination, which presents a major problem in drinking water treatment. 5,6 Removal of HAs has long been of concern in water treatment due to their diverse reactivity and abundance in natural waters. Ozone, as a powerful oxidizing reagent, could react with the organic matter present in water through different mechanisms involving direct molecular reactions and hydroxyl radical (OH . )…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, HAs are precursors of disinfection byproducts (DBPs) such as halogen-organics that are formed after water chlorination, which presents a major problem in drinking water treatment. 5,6 Removal of HAs has long been of concern in water treatment due to their diverse reactivity and abundance in natural waters. Ozone, as a powerful oxidizing reagent, could react with the organic matter present in water through different mechanisms involving direct molecular reactions and hydroxyl radical (OH . )…”
Section: Introductionmentioning
confidence: 99%
“…While our 90-day study was not suggestive of any thyrotoxicity of the test item, in the study by Daniel et al thyroid lesions that could be indicative of the presence of a goitrogen in their test item or iodine sequestration by HA in the gastrointestinal track were observed [ 31 ]. Because some known goitrogenic substances have been reported as degradation products of humic substances [ 68 ], further investigations into the toxicological potential of blk.…”
Section: Discussionmentioning
confidence: 56%
“…We investigated the repeated-dose toxicity of our test item in rats and observed several statistically significant alterations in various parameters that were of low magnitude and considered to be without toxicological concern. Interestingly, with respect to effects of humic substances on the thyroid, Daniel et al observed an increased incidence in histological thyroid lesions (colloid depletion, minimal severity and follicular cysts) in male Sprague-Dawley (SD) rats administered a single dose of a commercial HA preparation (Fluka, Switzerland) as a control substance in a subchronic toxicity study of the same HA subjected to ozonation (O 3 -HA) or subjected to both ozonation and chlorination (O 3 /Cl 2 -HA); however, thyroid hormone levels were not measured in the study [ 31 ]. Thyroid colloid depletion was also observed in high-dose O 3 /Cl 2 -HA group males at lower incidence while thyroid lesions were not observed in the buffered water control or O 3 -HA high-dose groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that they contain both aromatic and aliphatic components with primarily carboxylic and phenolic functional groups, HAs are very resistant to biodegradation and contribute to the brownish-yellow color of water [1,2]. Most significantly, HAs are precursors of disinfection by-products (DBPs) such as halogen-organics that are formed after water chlorination, which causes a major problem in drinking water treatment [3]. Several oxidation techniques for the treatment of HAs from water have been introduced, e. g., photocatalytic oxidation [4,5], ozonation [6 -8], and the coupled system of photo-catalysis and ozonation [9].…”
Section: Introductionmentioning
confidence: 99%